Les post-keynésiens et la monnaie endogène - Lavoie, Marc (L'Actualité économique, 1982)
AbstractThis paper attempts to identify the peculiar aspects of post-Keynesian monetary theory. In a modern production economy, the growth of the stock of money is an essentially endogenous process. It results from the Financial needs of firms to pay out incomes to households. It follows that monetary policy is asymmetrical: central banks cannot increase the rate of growth of the money supply, they can only restrain it. Hence, inflation is never and nowhere a monetary phenomenon.